Feed protein utilization and nitrogen emission of young and mature Kejobong goats fed different ratios of concentrate and forage - Farah Nabila; Vita Restitrisnani; Retno Adiwinarti; Agung Purnomoadi (Faculty of Animal Science, Universitas Brawijaya, 2021)
This study aimed to evaluate feed protein utilization and nitrogen emission of young and mature Kejobong goats fed different concentrations of concentrate and forage. Sixteen heads of male Kejobong goats consisted of eight heads young goats (5 months old) and eight heads mature goats (9 months old) with initial body weight (BW) of 14 ± 1.46 kg, and 22.3 ± 1.99 kg, respectively were arranged in a nested design. All goats were fed with two different rations of concentrate and forage (C30 = 30% concentrate: 70% forage and C70 = 70% concentrate: 30% forage). The data were analyzed using ANOVA procedure. This study showed that the average daily gain (ADG) did not differ (p>0.05) in both ages, but it differed (p<0.05) in concentrate levels. The ADG of goats fed C70 was significantly higher (p<0.05) than those of goats fed C30 in both ages. The digestible crude protein (DCP) of young and mature goats was similar (p>0.05), while there was a significantly difference (p<0.05) between the treatments. There were no effects of different ages of goats and concentrate levels on feed conversion ratio (FCR) (p>0.05). The different ages of goats and concentrate levels affected N retention (g/day) and total N2O emission (g/day). It was concluded that ADG, DCP and FCR did not differ in mature and young Kejobong goats, while young goats had less N2O emissions than mature goats. Goats fed 70% of concentrate improved their ADG, DCP, N retention (g/day) and produced less N2O emission.